(untitled) (Global Scientific Review, 2024)
The importance of the research is highlighted in clarifying the role of scout leaders in enhancing psychological security among the scout teams affiliated with the Thi Qar Education Directorate. The research problem lies in scout leaders’ role in enhancing psychological security among the scout teams affiliated with the Thi Qar Education Directorate. The goal of the research is to identify the extent to which the scout leader A course enhances psychological security among scout teams affiliated with the Thi Qar Education Directorate from the point of view of scout leaders. As the researcher used the research methodology, the descriptive method using the survey method, to suit the objectives of the research, in addition to the aspect of the correlational relationship, the research community was determined by the leaders of the scout teams in the Thi Qar Education Directorate, and the research community was identified by the leaders of the scout teams The researcher selected the research sample, which amounts to (190) scout team leaders in the Thi Qar Education Directorate, in a random manner, and their percentage is (42.34%) from the original community, as the most important conclusions were that the current questionnaire is a tool for identifying the levels of the role of the scout leader in enhancing Psychological security among the scout teams affiliated with the Thi Qar Education Directorate, analyzed and discussed, as the most important recommendations were adopting the questionnaire for the purpose of identifying the role of scout leaders in enhancing psychological security among the scout teams affiliated with the Thi Qar Education Directorate, spreading the culture of scouting activities among school administrations and society by involving them in National Scouting events and celebrations as guests of honor to view the work of Scout team leaders Their participating teams, knowing the great benefit they bring to scouts, issuing introductory and educational books and wall posters, and distributing them to attendees .